2
Пошаговое объяснение:
11111111111111111111111111111111111111111111111 | 9
- 9 | 12345678901234567890
21
- 18
31
- 27
41
- 36
51
- 45
61
- 54
71
- 63
81
- 81
11
- 9
21 (ост 2)
- 24 + 6х + 4у + 20 = 2
6х + 4у - 4 = 2
6х + 4у = 6
у = (6 - 6х)/4
у = 6(1 - х)/4
у = 3/2*(1-х)
Пусть х = 1, тогда у = 0
ответ: (1;0)
4)
4(x+6)+y(x+2)=16+y(x+6)
4х + 24 + ху + 2у = 16 + ху + 6у
4х + ху + 2у- ху - 6у = 16 - 24
4х - 4у = -8
4(х - у) = - 8
х - у = - 2
у = х + 2
Пусть х = 0, у = 0+2 = 2
ответ: (0; 2)
3)
(x-3)+x(y+4)=-45+y(x-3)
х - 3 + ху + 4х = - 45 + ху - 3у
х + ху + 4х - ху + 3у = - 45 +3
5х + 3у = - 42
у = (- 42 - 5х)/3
Пусть х = 0, тогда у = -14
ответ: (0; - 14)
2)
11(1+x)-9(7-y)=-36
11 + 11х - 63 + 9у = - 36
11х + 9у - 52 = - 36
11х + 9у = 52 - 36
11х + 9у = 16
у = (16 - 11х)/9
Пусть х = 2, тогда у = -6/9 = - 2/3
ответ: (2; - 2/3)